Dampak Diskusi Online Terhadap Keterampilan Sosial Mahasiswa PGMI UIN Raden Intan Lampung - Amikratunnisyah, Amikratunnisyah; Istiningsih, Istiningsih; Sodiq, Ahmad (Jurnal Penelitian, 2022)
This study aims to determine the impact of online discussion methods on the social skills of PGMI UIN Raden Intan Lampung students. This type of research uses descriptive qualitative research. The objects in this study were online discussion and social skills, while the research subjects were students of PGMI UIN Sunan Raden Intan Lampung semester 1 of 52 respondents. This research was carried out when the researcher became an apprentice student as well as acting as a teaching assistant for the lecturer in the Morals of Tasawuf course at the PGMI Study Program UIN Raden Intan Lampung, which was held from 12 October 2022 to 21 December 2022. Data collection techniques in the form of questionnaires, observation, and semi-structured interviews. The data analysis techniques used were data reduction, data presentation, and conclusions. The results showed that the online discussion method applied at PGMI UIN Raden Intan Lampung had positive and negative impacts on students' social skills. The positive impacts of the online discussion method include: (1) improving skills in dealing with other people; (2) increase a sense of solidarity and good cooperation; (3) accustomed to organize and self-management of activities or tasks, (4) increase self-confidence, and; (5) improve the skill of complying with the rules. Meanwhile, the negative impact of this online discussion method is the low academic skills of students consisting of: (1) lack of understanding of lecture material; (2) the lack of fluency in student communication skills; (3) lack of interaction and liveliness in discussions between students.